Penyisipan Pesan Pada File Dokumen PDF Dengan Metode Pixel Value Differencing - Putra Abdi Surya (Graha Mitra Edukasi, 2023)
Data is a collection of facts that can be in the form of numbers, symbols or writing obtained through an object. Data can be confidential and can also be public which means that it can be published. Confidential data is data that is not made to be published, but for private circles, because the data is data related to the company or its personal data. However, sometimes confidential data is often blamed for use by other people or third parties by taking or stealing the data for their personal interests and bringing down other people or companies. Given the rapidly developing technology today, it is possible for everyone to create a new technology to manipulate or steal confidential data. To overcome this problem, it is necessary to create data security, so that confidential data owned by a person or company cannot be taken or misused. The data security technique used to overcome this problem is the steganography technique. PVD is an insertion method that works by finding the two closest value differences. The difference is then used to determine the amount of data that can be inserted based on the selected data range. By utilizing this method, an application can be designed that can be used to secure data, especially in the insertion of messages into pdf document files.